Psychological antecedents of hajj crowd scales: Content validation - Abdul Rahman, Shukran; Mohd Mahudin, Nor Diana; Shuib, Mohd Arif; Ahmad Hatta, Zulkarnain; Abdul Ghani, Noraida; Sulong, Jasni; Mohd Hashim, Intan Hashimah; Mat Saad, Zarina (Universiti Utara Malaysia, 2016)
This article reports the content validation exercise of items in five newly developed scales that measure the psychological antecedents of crowds during Hajj (i.e., Personality, Crowd Mood, Expected Crowdedness, Perceived Lawlessness, and Hajj Familiarity). This exercise is embarked to assess whether the items in the scales represent the content areas of the construct specified in the five scales; a concept referred to as content validity. The exercise provides evidences to test developers about the extent to which the items could be retained in a scale which is determined by the degree of experts' agreement. Fifteen subject matter experts have been engaged to rate the essentiality of an item in measuring a particular construct. They indicated whether the samples of items have adequately represented a particular dimension of the construct in question, after which the content validity ratio for each item was calculated. The values of content validity ratio provides evidence on the inclusion of an item in the scales, and, in turn, leads to the index for high content validity.